Can we mend fences?: A model of recovery processes of SME business-to-business relationships - Fleming Deirdre Mary; Tähtinen Jaana; Kelliher Felicity (Emerald, 2022)
Purpose This paper aims to develop a process model of business-to-business (B2B) relationship recovery after a transgression has placed the future of the relationship in doubt. The research questions ask, How are relationships recovered? and How does the relationship strength pre-transgression influence the recovery process? Design/methodology/approach The process model is empirically grounded with first-hand narratives of owner managers (OMs) and key personnel of Irish small and medium-sized enterprises (SMEs). Using the critical incident technique, 25 owner and manager interviews in 23 SMEs resulted in 48 recovery narratives. Findings The findings identify four types of outcomes flowing from two potential recovery process paths. The strength of the relationship pre-transgression and the desire to maintain the relationship influence the parties' actions during the recovery process and the status of the relationship subsequently. Research limitations/implications The authors acknowledge that each narrative in the data are the informants' construction of the phenomenon. The B2B relationship recovery process model offers OMs and SMEs a blueprint of what to expect, and how they might reach for recovery instead of the relationship ending. Originality/value Prior studies either treat recovery as a minor part of an ending process or focus on a single sub-process, leaving the overall process under-researched. This study contributes to the B2B relationship dynamics discussion with a processual view of the overall recovery process, including recovery sub-processes, paths and temporal outcomes in different types of relationships and takes into account the pre-transgression relationship.